Subcritical water extraction of antioxidants from mountain germander (Teucrium montanum L.) - Nastić, Nataša (2019)
In the present work, antioxidant compounds from Teucrium montanum were extracted by subcritical water. The influence of extraction temperature and pressure on antioxidant activity of extracts has been investigated in terms of extraction yield (EY), total phenolic content (TPC), and DPPH-radical scavenging activity (DPPH-RSA) and ferric reducing antioxidant power (FRAP). Additionally, the compounds responsible for the antioxidant activity were identified and quantified by high performance liquid chromatography (HPLC). The highest EY (42.63%), TPC (174.61 ± 4.09 mg GAE/g DE) and antioxidant activity by DPPH-RSA (176.23 ± 8.76 mg TE/g DE) and FRAP (141.71 ± 5.21 mg AAE/g DE) were seen in extracts obtained at temperature of 160 °C and pressure of 10 bar. HPLC analysis revealed that naringin and gallic acid were the principle antioxidant compounds in subcritical extracts. According to the results, SWE has a great potential in exploitation of natural sources of bioactive compounds and production of pharmacologically-active fractions.